PERANCANGAN BRAND ACTIVATION DAN MEDIA PROMOSI UNTUK THERAPEUTIC - Karsena, Yemima Judithia; Budi, Hutomo Setia (Jurnal VICIDI, 2021)
Currently, environmental issues are a sensitive matter and are widely discussed in the world and in Indonesia. Environmentally friendly products have started to be widely used and have become a new lifestyle for several groups of people. Many business actors take this opportunity to start a business which at the same time invites the public to care more about environmental health. Therapeutic is a new business created because of the founder’s awareness of environmental issues that are currently happening. Carrying eco-friendly products, Therapeutic sells natural soap bar and scented products that are made from natural ingredients and do not cause environmental damage, as well as applying the concepts of less-waste, reuse, and eco-lifestyle. As a new brand that stands in the midst of a pandemic like today, Therapeutic has several obstacles, namely in Indonesia there have been many similar products or businesses that will cause Therapeutic to lose competitiveness and lose name when faced with competitors. In addition, Therapeutic still needs trust from consumers, which is very necessary for the types of products and systems from Therapeutic. From the problems faced, Therapeutic conducted research to find out what marketing strategies and promotional media were right to increase brand awareness. The formulation of the problem in this study is how the brand activation strategy and promotional media are in accordance with the target market to increase Therapeutic brand awareness in social media. This research uses qualitative and quantitative methods in collecting data. The qualitative method is carried out by interviewing several experts and extreme users of eco-lifestyle actors to find data on how to carry out the right promotion. The quantitative method is carried out by surveying the Indonesian people to find out what social media platforms are most effective in promoting. The results of this study concluded that the right brand activation strategy for Therapeutic is by carrying out activities that can attract public interest such as workshops, so that the activities carried out can simultaneously introduce products and brands and provide education. The right social media platform to promote Therapeutic activation is Instagram. Keywords: Brand Activation, Eco-Lifestyle, Eco-Friendly, Social Media.